2004
DOI: 10.1111/j.1365-2419.2004.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Life histories of Eucalanus bungii and Neocalanus cristatus (Copepoda: Calanoida) in the western subarctic Pacific Ocean

Abstract: Life cycles of the large suspension-feeding copepods, Eucalanus bungii and Neocalanus cristatus were investigated by seasonal sampling in the western subarctic Pacific. Eucalanus bungii has a diapause from August to March at copepodite stages between copepodite 3 (C3) and C6 female. We propose that individuals with early birth dates are young of overwintering C5 and C6-females that develop to C4 in their birth year, while individuals with late birth dates are young of overwintering C4 that develop to C3 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 22 publications
3
63
0
Order By: Relevance
“…On the other hand, the N. plumchrus development occurs in the peak or declining season of the spring bloom period when it progresses rapidly through the C1-C4 stages without lipid accumulation. Tsuda et al (2004) revealed that C2-C4 individuals of N. cristatus had an oil sac or only droplets, but it rarely exceeded 10% of the prosome length, and lipid storage was mainly observed in the C5 stage. C1 individuals showed higher lipid storage, however, this storage is considered to originate from egg yolk (Saito and Tsuda, 2000) although the lipid composition of egg yolk is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the N. plumchrus development occurs in the peak or declining season of the spring bloom period when it progresses rapidly through the C1-C4 stages without lipid accumulation. Tsuda et al (2004) revealed that C2-C4 individuals of N. cristatus had an oil sac or only droplets, but it rarely exceeded 10% of the prosome length, and lipid storage was mainly observed in the C5 stage. C1 individuals showed higher lipid storage, however, this storage is considered to originate from egg yolk (Saito and Tsuda, 2000) although the lipid composition of egg yolk is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…During this bloom period, the main population of N. cristatus undergoes a rapid development to stage C5 at the surface, and then migrates in summer/autumn to deeper layers (below 500 m) to undergo diapause. Overwintering C5 specimens develop to adults, spawn during autumn to winter at depth and lipid-rich eggs and nauplii ascend to the surface along with their development in spring (Kobari and Ikeda, 1999;Tsuda et al, 2004). Thus, N. cristatus depends on the lipids stored during the previous spring bloom for somatic maintenance and reproduction as do other Neocalanus species in the subarctic Pacific Ocean (Fulton, 1973;Miller et al, 1984;Saito and Tsuda, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations